Managing cultural change in public libraries : Marx, Maslow, and management - Pateman, John, 1956-; Pateman, Joe; Williment, Ken; Vincent, John, 1948- (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"In Managing Cultural Change in Public Libraries, Pateman draws on the ideas of Marx and Maslow to present an ambitious 'analytical framework', which, he says, can be used to create bold public-library strategies, structures, and systems. Pateman argues for radical--but sustainable--transformations in public libraries. In particular, he envisions: - Strategies that are focused on users with the greatest needs, and that have social justice at their core. Public libraries can be converted, Pateman says, from institutions of social control into agencies of social change. - Non-hierarchical staff structures, or 'holocracies' in which organizational positions are matched to individual strengths, talents, and skills. - Service structures which are flexible and are able to respond quickly and creatively to changing community needs. - Systems which are 'enabling' with policies, processes, and procedures which permit community needs to be identified and met. Prescriptive manuals will be superseded by parameters to encourage innovation and creativity. - Evaluation and assessment of library services which no longer rely on 'one-dimensional and misleading metrics' such as circulation, membership, and visits but, rather, depend on a more qualitative approach. Managing Cultural Change in Public Libraries will be of particular interest to advanced students, practitioners, and policymakers working in Library and Information Science. It offers hope of a world where 'every section of the community will be fully involved and engaged in the planning, design, delivery, and evaluation of library services' and of 'libraries which are inclusive and truly open to all'"--
Foreword / by Ken Williment -- Foreword / by John Vincent -- Analytical Framework -- The Traditional Library -- The Community Led Library -- The Needs Based Library -- Conclusions and Ways Forward
OCLC-licensed vendor bibliographic record.
Keywords: Public libraries -- Great Britain -- Administration; Public services (Libraries) -- Great Britain; Library planning -- Great Britain; Organizational change; LANGUAGE ARTS & DISCIPLINES / Library & Information Science / General; LANGUAGE ARTS & DISCIPLINES / Library & Information Science